The oestrus cycle of Zebu and Sanga breeds of cattle in Central Africa - Rakha, A.M.; Igboeli, G.; Hale, D.H. (Bioscientifica, 1970)
The oestrus cycle and its manifestation in the Angoni, Barotse and Boran cattle are investigated. The time of onset and manifestation of oestrus and ovulation are observed, and changes in the size, colour, appearance and contents of the cervical organs reported.